1998
DOI: 10.2307/2991913
|View full text |Cite
|
Sign up to set email alerts
|

Informed Choice and Decision-Making in Family Planning Counseling in Kenya

Abstract: Context: Family planning programs have long endorsed the principle of informed choice as a way of ensuring that clients select a method that best meets their needs. There has been little research, however, that examines how, or whether, family planning clients make informed decisions. Methods: Interactions between female family planning clients and clinic-and community-based providers at 25 service delivery sites in Kenya were audiotaped over a 9-15 day period. Transcripts of 176 counseling sessions were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 4 publications
0
69
0
2
Order By: Relevance
“…2 A situation analysis of Nairobi clinics showed that fewer than 50% of new clients w e re provided with information on contraindications to or side effects of their chosen method. 3 Further situation analyses conducted in 12 African countries indicated that the percentage of clients informed about both how to use their method and its potential side effects ranged from lows of 5% in Tanzania and 22% in Burkina Faso, to highs of 64% in Kenya and 68% in B o t s w a n a .…”
Section: Length Of Counseling Sessions and The Amount Of Relevant Infmentioning
confidence: 99%
“…2 A situation analysis of Nairobi clinics showed that fewer than 50% of new clients w e re provided with information on contraindications to or side effects of their chosen method. 3 Further situation analyses conducted in 12 African countries indicated that the percentage of clients informed about both how to use their method and its potential side effects ranged from lows of 5% in Tanzania and 22% in Burkina Faso, to highs of 64% in Kenya and 68% in B o t s w a n a .…”
Section: Length Of Counseling Sessions and The Amount Of Relevant Infmentioning
confidence: 99%
“…En este sentido, otros estudios son congruentes con nuestros resultados al señalar que, cuanto mayor es el conocimiento de MAC, mayor es su uso, particularmente entre los hombres. 13,15,25 Es evidente que tanto hombres como mujeres necesitan de mayor información sobre MAC, particularmente modernos, pues como mostró este estudio, si bien más de 90% de hombres y mujeres refirieron conocer sobre MAC, al indagar sobre sus características y uso, este porcentaje descendió 50%. Por otro lado, en las parejas que refirieron no usar MAC modernos, los hombres en su mayoría lo hacían por temor a la infidelidad de su pareja.…”
Section: Discussionunclassified
“…With the programmatic emphasis in the past several decades on informed choice in family planning, some providers have shifted to the other end of the spectrum, giving clients standard or routinized information on all available methods and leaving the client to make decisions unaided [4]. In between these two extremes lies a model of client-centered care where the decision-making process is shared by the client and provider: the provider facilitates the process and the client actively participates.…”
Section: Introductionmentioning
confidence: 96%